2018
DOI: 10.1097/j.pain.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous pain modulation in chronic orofacial pain: a systematic review and meta-analysis

Abstract: Abnormal endogenous pain modulation was suggested as a potential mechanism for chronic pain, ie, increased pain facilitation and/or impaired pain inhibition underlying symptoms manifestation. Endogenous pain modulation function can be tested using psychophysical methods such as temporal summation of pain (TSP) and conditioned pain modulation (CPM), which assess pain facilitation and inhibition, respectively. Several studies have investigated endogenous pain modulation function in patients with nonparoxysmal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 79 publications
1
62
0
Order By: Relevance
“…Inability to induce pain inhibition using a CPM testing paradigm in both fibromyalgia cases and healthy controls has been reported recently, leading the authors of that study to speculate about the possibility of positive publication bias influencing the currently accepted significance of CPM for chronic pain conditions . This reasoning is supported at least in part by the publication bias identified for CPM studies of TMD cases reported in a meta‐analysis recently done by our group …”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Inability to induce pain inhibition using a CPM testing paradigm in both fibromyalgia cases and healthy controls has been reported recently, leading the authors of that study to speculate about the possibility of positive publication bias influencing the currently accepted significance of CPM for chronic pain conditions . This reasoning is supported at least in part by the publication bias identified for CPM studies of TMD cases reported in a meta‐analysis recently done by our group …”
Section: Discussionmentioning
confidence: 53%
“…The present study specifically controlled for gender, age and avoidance of acute pain medications intake 24 hours prior to testing, while data on time of the day testing occurred, caffeine and other pain medications intake and menstrual cycle phase were recorded, with no significant differences between TMD cases and control groups. Given these factors, it is possible that EPM assessment using TSP and CPM testing protocols as done in the present and previous studies may not be sensitive enough to distinguish chronic TMD patients from pain‐free controls. Reliability of EPM testing has been challenged recently, and there is a need for further studies to refine EPM testing methodology in order to improve its reliability.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations